Rétroaction dans les processus numériques de conception - Sébastien Bourbonnais (Netcom)
The computer tools used by architects have been improved significantly over the past 60 years, and they have evolved according to a complex scheme that embraces many concerns both within and outside the architectural community. By focusing on the ability of these different tools to return information to designers, by feedbacks, this paper will examine the different historical trends that have guided these improvements and identify the implications that these technologies have had on architectural design processes.This historical review shows that the arrival of digital technologies has raised many questions about the constitution of design processes, as well as the place to be given to these tools. The goal is to show that the knowledge embedded by the various computer programs will have led to a real overhaul of design knowledge, as part of the implementation of a new epistemology, driven by digital design processes.